The functional and health related quality of life outcome on severe traumatic brain injury in two east coast hospitals : a COHORT study - Nor'ain Abdul Rashid (Kulliyyah of Nursing, International Islamic University Malaysia, 2018)
Traumatic brain injury (TBI) is the most important medical and socioeconomic problem and is the top cause of death in the young adult. Severe TBI survivors show physical and functional improvement but remain with cognitive and psycho-social problem throughout recovery. However, the long-term impact of severe TBI survivors in Malaysia is still lacking. The main objective of this study is to measure the functional and health related quality of life outcome of severe TBI survivors within 6 months post-injury. A cohort study was done on 33 severe TBI survivors from Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang and Hospital Sultanah Nur Zahirah (HSNZ) Kuala Terengganu. The functional assessment of Glasgow Outcome Scale Extended (GOSE) and Quality of Life after Brain Injury (QOLIBRI) were measured within a 6 months period. The participants mean age was 31.79 ranging from 16 to 73 years old. The result of this study shows that GOSE score and QOLIBRI result improved within 6 months post-injury. The GOSE score showed that within 3 months after discharge from the hospital, all the participants were still poorly recovered, n=33 (100.0%). Meanwhile, after 6 months being discharged from the hospital, 48.5% of the participants scored a good recovery score. Logistic regression analysis was conducted to look for predicting factors in the TBI survivors' functional outcome. The full model was statistically significant, ² (5, N= 33) = 29.09, p< 0.001, and the LOS in the ICU (p=0.049, odds ratio = 6.062) and the duration of being on the ventilator (p=0.048, odds ratio = 0.083) become the predictors for the functional outcome. In the QOLIBRI result, age and duration on the ventilator showed a negative correlation to the QOLIBRI result. Independent T-test showed a significant difference in the GOSE scores for poor recovery (M= 31.88, SD = 23.65) and good recovery (M= 75.63, SD = 14.23; t (26.49) = - 6.48, p < 0.001 (two-tailed) to the QOLIBRI result. The good recovery group has high QOLIBRI resulted due to the satisfied health related quality of life. TBI survivors often have a long-term recovery process that may be influenced by different factors. In order to assist the TBI survivors to go through their recovery, the outcome measure with a more holistic assessment should be emphasized to enhance more useful results. Furthermore, it would be beneficial in the future to undertake longitudinal research studies on the TBI survivors' to gain a more accurate result on their long-term outcome following the injury.